2006
DOI: 10.1071/fp06051
|View full text |Cite
|
Sign up to set email alerts
|

A comment on the quantitative significance of aerobic methane release by plants

Abstract: Abstract. A recent study by Keppler et al. (2006; Nature 439, 187-191) demonstrated CH 4 emission from living and dead plant tissues under aerobic conditions. This work included some calculations to extrapolate the findings from the laboratory to the global scale and led various commentators to question the value of planting trees as a greenhouse mitigation option. The experimental work of Keppler et al. (2006) appears to be largely sound, although some concerns remain about the quantification of emission rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
94
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 20 publications
4
94
1
Order By: Relevance
“…Keppler et al (2006) made the first attempt to extrapolate the magnitude of this newly discovered CH 4 source of plants on measured CH 4 emission rates and NPP (net primary production of roots and shoots) and suggested a range of 62e236 Tg CH 4 yr À1 from plants. However, it seems that the magnitude of this source has been overestimated because of the following reasons: (1) the involvement of plant roots in the process and the extent that roots contribute to CH 4 production have not been defined, whereas the NPP allocated to roots was included in the calculation; (2) the loss of vegetation biomass during the growing season and plant selfshading may cause uncertainties (Kirschbaum et al, 2006;Megonigal and Guenther, 2008); (3) the length of the growing season was multiplied twice when multiplying the measured leaf emission rate by the annual growth rate and growing season length (Parsons et al, 2006).…”
Section: Implications For the Regional Ch 4 Budgetmentioning
confidence: 99%
See 2 more Smart Citations
“…Keppler et al (2006) made the first attempt to extrapolate the magnitude of this newly discovered CH 4 source of plants on measured CH 4 emission rates and NPP (net primary production of roots and shoots) and suggested a range of 62e236 Tg CH 4 yr À1 from plants. However, it seems that the magnitude of this source has been overestimated because of the following reasons: (1) the involvement of plant roots in the process and the extent that roots contribute to CH 4 production have not been defined, whereas the NPP allocated to roots was included in the calculation; (2) the loss of vegetation biomass during the growing season and plant selfshading may cause uncertainties (Kirschbaum et al, 2006;Megonigal and Guenther, 2008); (3) the length of the growing season was multiplied twice when multiplying the measured leaf emission rate by the annual growth rate and growing season length (Parsons et al, 2006).…”
Section: Implications For the Regional Ch 4 Budgetmentioning
confidence: 99%
“…Several subsequent scaling-up estimates were achieved using different assumptions, but the data for leaf emission rates were collected during the original study ) using bottom-up approaches (Butenhoff and Khalil, 2007;Houweling et al, 2006;Kirschbaum et al, 2006;Parsons et al, 2006) (Table 2). By assuming UV radiation-induced CH 4 emissions from pectin as representing foliar CH 4 emissions, Bloom et al (2010) suggested a global contribution of 0.2e1.0 Tg plantderived CH 4 yr À1 .…”
Section: Implications For the Global Ch 4 Budgetmentioning
confidence: 99%
See 1 more Smart Citation
“…Together, previous modeling studies suggest rice paddies and wetlands can release 100-380 Tg CH 4 yr −1 to the atmosphere. Further, recent studies identified a new source of tropical methane from nonwetland plants that could add as much as 10-60 Tg CH 4 yr −1 to the global budget (Keppler et al, 2006;Kirschbaum et al, 2006), although this source has been disputed and is still poorly quantified (Dueck et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The global methane production rates from living plants were estimated to be 62-236 Tg CH 4 year −1 , which may have a considerable effect on the global methane budget. This study generated a vigorous scientific debate and many subsequent studies were performed (e.g., Kirschbaum et al 2006;Kitaoka et al 2007;Beerling et al 2008;Kirschbaum and Walcroft 2008;Bowling et al 2009). In subsequent experiments, emission rates were found to be quite distinct in each experiment (e.g., Keppler et al 2006;Kirschbaum et al 2006;Kitaoka et al 2007), and some studies failed to measure any emissions (Beerling et al 2008;Kirschbaum and Walcroft 2008).…”
Section: Introductionmentioning
confidence: 99%